The Use of Smartphone To Process Personal Medical Record By Using Geographical Information System Technology - Go Frendi Gunawan, Subari, (PROCEEDING IC-ITECHS 2014, 2014)
In this era medical record is focussed on how to arrange medical record document. Thestatus of manual medical record will be kept on the storage, the media like paper is very easy to be broken and lost. Therefore the information of  medical record data will be difficult to be gotten completely, moreover the file of medical record especially for using personal is not easy to be kept.How the people face the improvement in using the gadget and also smartphone. it should be cope with how to optimalize smartphone technology used by people by using correct information  media  in  the  implementing  electronic  medical  record  for  each  person.  This research  design  also  includes  the  technology  of  geographical  information  system  for  the spatial data of private doctor, hospital, medical laboratorium and related object for every using smartphone.This research will result the running application on the smartphone that can operate and manage individual medical record. It can be integrated online on the center of health and give recommendation and retrieval information about medical note for the hospital, private doctor or other health service. The invention of this application can process the medical record data from some deseases fast, more detail and easy, also the geographical visualization for the related health service.